Sustainable pavement construction through reclaimed asphalt pavement and supplementary cementitious materials - Ranjitham Mariappan; Jeyapriya Subanantharaj Palammal; Balu Soundara; Selina Ruby Gurujothi (European Journal of Environmental and Civil Engineering, 2026)

Concurrent small intestinal neoplasia and large colon volvulus in a standardbred yearling - V. Barros; J. Cascais; K. Holbert; R. Ruby; R. Freeland (Journal of Equine Veterinary Science, 2026)

From fragments to full pictures: how long-read sequencing platforms are revolutionizing oncology research - Ruby Dhar; Abhibroto Karmakar; Abhishesh Kumar Badal; Om Saswat Sahoo; Prasmita Paul; Isha Goel; Arnab Nayek; Karthikeyan Pethusamy; Ashikh Seethy; Subhradip Karmakar (Molecular Biology Reports, 2026)

Disparities in Gallbladder Cancer: Epidemiology, Molecular Mechanisms, and Clinical Implications - Om Saswat Sahoo; Gurpeet Singh Gill; Arnab Nayek; Nidhi Bhardwaj; Kailash Chand Kurdia; Saurabh Galodha; R Chetan; Ruby Dhar; Subhradip Karmakar (Molecular Biology Reports, 2026)

Comprehensive transcriptomic analysis highlights immune and cell-cycle dysregulation in Diamond-Blackfan Anaemia - Isha Goel; Ashikh Seethy; Karthikeyan Pethusamy; Deepak Kumar; Ruby Dhar; Tulika Seth; Subhradip Karmakar (Molecular Genetics and Genomics, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Evolutionary co-option of endogenous retroviruses: syncytins as regulators of placental development and disease - Anamta Gul; Om Saswat Sahoo; Neha Kashyap; Sunil Singh; Anubhuti Rana; Lavanya Gupta; Swati Ajmeriya; Indrani Mukherjee; Ruby Dhar; Nihar R. Nayak; Subhradip Karmakar (Molecular Biology Reports, 2026)

Plant-based eating: Exploring at home vs dining out behaviours across consumer segments - Carla Riverola; Stephen Harrington; Ozgur Dedehayir; Matthew B. Ruby (Appetite, 2026)

Adsorption-desorption nexus of biowaste-derived biochars towards potentially toxic elements: Unveiling challenges and paving paths for the large-scale mining and industrial soil applications - Javed Nawab; Ruby; Amir Hamza; Muhammad Waqas; Cosimo Magazzino; Matthias Kleinke; Irfan Ullah (Biomass and Bioenergy, 2026)

Divergent Environmental Niches and Climate Vulnerabilities of Jonah Crab ( Cancer borealis ) and Atlantic Rock Crab ( Cancer irroratus ) - Everett J. Rzeszowski; Ruby Krasnow; Damian C. Brady (Fisheries Oceanography, 2026)
Jonah crab and Atlantic rock crab in the United States are currently assessed by National Oceanic and Atmospheric Administration climate change vulnerability assessments under the category Cancer crabs due to a dearth of species‐specific information across the attributes assessed. These species are frequently bycatch in the American lobster fishery and have low landed volume in comparison to larger Northeast US commercial fisheries. Here, we developed species distribution models using abundance, bottom temperature, and bottom salinity from Northeast Fishery Science Center Bottom Trawl data and calculated species‐specific environmental suitability indices. We used interpolated data to hindcast (1992–2024) environmental suitability in the five Jonah crab stocks for each species. Then, using similar methods, environmental suitability was forecasted from bottom temperature and bottom salinity conditions from 2075 to 2094 under RCP 8.5 climate conditions. This analysis found that Jonah crab occupies a narrow, stable niche, with optimal temperatures of 9°C–12°C in both seasons and habitat 150–350 m deeper than Atlantic rock crab, while Atlantic rock crab tolerates far larger swings, with the OSNE stock shifting optimal temperature by 11°C (5°C to 16°C) and salinity by 7 units between spring and fall. By identifying these differences, we show that Jonah crab's narrower thermal and salinity tolerance likely makes it more sensitive to climate change than the broadly tolerant Atlantic rock crab, refining species‐specific inputs for climate change vulnerability assessments and each species' potential as a long‐term fishery target.

Implementing area-based management of vulnerable marine ecosystems in areas beyond national jurisdiction: A South Pacific case study - Ashley A. Rowden; Fabrice Stephenson; Martin Cryer; Carolyn J. Lundquist; Owen F. Anderson; Matthew Bennion; Andrew Biggerstaff; Tiffany Bock; Tom Brough; Lee Georgeson; Alexandra Macdonald; Marco Milardi; et al. (Ocean & Coastal Management, 2026)

An immunoinformatics approach to study the physicochemical properties and efficacy of mRNA-1273 against SARS-CoV-2 - Ruby Srivastava (Next Research, 2026)

Surveillance for campylobacteriosis and a comparative detection of Campylobacter spp. by conventional and molecular methods in India - Jaspreet Mahindroo; Chandradeo Narayan; Harpreet Kaur; Md Yousuf; Ruby Jain; Balvinder Mohan; Neelam Taneja (Next Research, 2026)

Assessment of growth and physiological effects of dietary Arthrospira platensis in broiler chickens - Zain Ul Abideen; Muhammad Zeshan Haider; Muhammad Kashif Zaman; Muhammad Farooq; Amin F. Majdalawieh; Imad A. Abu-Yousef; Tahira Ruby; Aleem Ahmed Khan (Livestock Science, 2026)

Corrosion protection of copper in H2SO4 by Acer palmatum leaf extract - Qihui Wang; Lijia Liu; Jun Wang; Qi Huang; Qinrong Sun; Wei Feng; Ruby Aslam; Yi Sun; Zhitao Yan (International Biodeterioration & Biodegradation, 2026)

Dependence of subseasonal to seasonal precipitation prediction on atmospheric and land initial conditions in the Energy Exascale Earth System Model - Dongze Xu; Zhaoxia Pu; Shixuan Zhang; Jeffrey Anderson; L. Ruby Leung (Climate Dynamics, 2026)

Sequential recovery of fish silage lipids and proteins for biodiesel production and marine microalgae cultivation - Regina M. González-Balderas; Isabel Martínez-Apodaca; Julio C. Sacramento-Rivero; Mariela C. Lope Navarrete; Ruby Valdez-Ojeda (Algal Research, 2026)

Temperature Influences Pseudocapillaria tomentosa Infections in Zebrafish, Danio rerio (Hamilton 1822) - Connor Leong; Ruby Scanlon; Corbin J. Schuster; Michael L. Kent; Thomas J. Sharpton (Journal of Fish Diseases, 2026)
Poikilothermic organisms like fish are key economic drivers in aquaculture and the ornamental fish trade. Climate change impacts the health of fish because poikilothermic hosts experience the same temperature as their environment, making temperature a critical determinant of parasite infection dynamics. Pseudocapillaria tomentosa , a capillarid nematode infecting approximately 20% of zebrafish research facilities, provides an excellent model for investigating temperature effects on nematode development because zebrafish can tolerate a wide temperature range. We examined how water temperature influences egg development and worm maturation across the zebrafish's tolerable thermal range (13°C–35°C). Eggs held at 4°C or 13°C failed to larvate but resumed development when returned to 28°C. Larvation increased at 35°C, though infectivity was reduced in larval zebrafish. In adult zebrafish, cold water (13°C) slowed worm development for up to 3 months; only immature larvae were observed even at 102 days post‐exposure. Returning these fish to 28°C triggered rapid maturation, with gravid females appearing within 1 month. Conversely, fish held at 35°C had reduced worm burdens and arrested maturation compared to 28°C controls, with development resuming after temperature reduction. These findings align with field observations of seasonal P. tomentosa dynamics in temperate climates.

Mitogenomic Architecture and Phylogenetic Insights Shed Light on the Matrilineal Evolution of the Mahseer Fish Neolissochilus sumatranus (Cyprinidae: Torinae) in Southeast Asia - Sekar Larashati; Angkasa Putra; Sarifah Aini; Gema Wahyudewantoro; Mey Ristanti Widoretno; Dwi Febrianti; Huria Marnis; Imam Civi Cartealy; Tri Widiyanto; Ruby Vidia Kusumah; Anik Budhi Dharmayanthi; Muhammad Hilman Fu’adil Amin; et al. (Biochemical Genetics, 2026)

Systematic evaluation of atmospheric forcing, surface datasets, and mesh effects on kilometer-scale land surface and river modeling - Lingcheng Li; Gautam Bisht; Donghui Xu; Dalei Hao; Chang Liao; Dongyu Feng; Zeli Tan; Hongyi Li; Mingjie Shi; Tian Zhou; L. Ruby Leung (Journal of Hydrology, 2026)

From urban biosolids to biochar and nanobiochar: A scoping review of environmental applications and circular resource recovery - Sheila Abreu Mourão; Alexandre Santos Pimenta; José Cola Zanuncio; Fernanda Helfer; Ivan Gratchev; Ruby Naomi Michael (Journal of Environmental Management, 2026)

Prenatal and early postnatal lead exposure and later adulthood BMI: The Saint Louis baby tooth – Later life health study - Joyce J.Y. Lin; Ruby Hickman; Michael Leung; Justin Farmer; Ian W. Tang; Kaleigh McAlaine; Tracy Punshon; Brian P. Jackson; Felicitas B. Bidlack; Joseph J. Mangano; Marc G. Weisskopf (Environmental Research, 2026)

PFAS immobilization with soil amendments – How immobilized is immobilized? - Albert L. Juhasz; Tanya Cáceres; Ruby Jones; Farzana Kastury; Mahima Seeborun; Carina Herde; Michelle Cavallaro (Environmental Pollution, 2026)

Mutagenic and carcinogenic potency determinations for NDMA support the cumulative dose assumption underpinning the less-than-lifetime Threshold of Toxicological Concern - John W. Wills; Angela White; Danielle S. G. Harte; Ruby Buckley; James S. Harvey; Anthony M. Lynch (Archives of Toxicology, 2026)

Shifts in subsurface oxygen transport and consumption patterns in a restored coastal flood plain over five years - Emilio Grande; Ruby N. Ghosh; Charles McIntire; Michael J. Freeman; Peter Regier; Nicholas D. Ward (Limnology and Oceanography, 2026)
Groundwater dissolved oxygen (DO) variability in coastal systems remains poorly understood despite its importance for biogeochemical cycling and ecosystem modeling. This study investigates temporal variability in groundwater DO and its hydro‐climatic drivers across timescales (hourly to seasonal) in a coastal floodplain at Beaver Creek, Washington, USA, a site transitioning from a freshwater forest to brackish tidal wetland following restoration of tidal influence. Using 5 years of high‐frequency (5‐min) hydro‐meteorological and continuous groundwater DO data, we applied wavelet and information theory analyses to disentangle the role of different drivers (e.g., groundwater levels, temperature, precipitation, among others) on DO dynamics. Monitoring was initiated 5 years after the site was restored but prior to subsurface conditions reaching a new steady state. We found that DO pulses related to tidal flooding events were most frequent during earlier water years, dominated by hourly, daily and multiday variability. In later years both the frequency and magnitude of these DO pulses decreased, resulting in more prolonged subsurface anoxia. These shifts in DO patterns reflect gradually changing subsurface biogeochemical conditions as the system continues to fully transition from lowland forest to brackish wetland 10 years after restoration. This study highlights the critical role of timescale‐specific analyses in understanding wetland biogeochemistry by identifying dominant drivers of DO variability and linking them to ecosystem transitions. Our scale‐aware approach offers a framework for evaluating ecosystem responses to climate change, sea‐level rise, and restoration efforts in tidal wetlands.

Socio-technical opportunities for developing sustainable continence healthcare: A systematic literature review - Ruby Bubinek; Victoria Ankerstjerne; Morten Krogh Petersen; Ali Ebrahimi; Ciprian Cimpan (Sustainable Production and Consumption, 2026)

Correction: Establishment of a Cre-rat resource for creating conditional and physiological relevant models of human diseases - Huimin Zhang; Qi Zheng; Ruby Yanru Chen-Tsai (Transgenic Research, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Functional auxin signaling and phosphorus acquisition induced in planta by the extremophile bacterium Pseudomonas extremaustralis - Carola Agranatti; Jose G. Ibarra; Mariana B. Galeano; Ruby Terranova; Manuel S. Godoy; Nancy I. López; Martiniano M. Ricardi; Paula M. Tribelli (Rhizosphere, 2026)

Intelligent corrosion protection of carbon steel with magnetic and pHresponsive inhibitor - Qihui Wang; Jialin Chen; Jinmei Zhao; Qi Huang; Wei Feng; Yi Sui; Ruby Aslam; Yi Sun; Wenjing Yang (Journal of Environmental Chemical Engineering, 2026)

Early-life neighborhood resources and later-life cognitive function - Justin G. Farmer; Ian W. Tang; Peter James; Laura D. Kubzansky; Rajarshi Mukherjee; Ruby Hickman; William Kessler; Laura T. Germine; Marc G. Weisskopf (Environmental Research, 2026)

Tourists’ Circular Behavior and Its Determinants: Pathways Toward Sustainable Destinations - Swati Naik; Ruby S. Chanda (Circular Economy and Sustainability, 2026)

Postharvest γ-Aminobutyric Acid Treatment Modulates Antioxidant Metabolism and Delays Quality Deterioration of Litchi Fruit - Nilanksha; Preeti Singh; Hidayatullah Mir; Ruby Rani; Mohammed Wasim Siddiqui; Fozia Homa; Shashi Prakash (Applied Fruit Science, 2026)

miRNA–mRNA network analysis reveals novel post-transcriptional regulators and therapeutic targets in coronary artery disease - Prasmita Paul; Om Saswat Sahoo; Rajiv Narang; Abhishesh Kumar Badal; Arnab Nayek; Ruby Dhar; Oindrilla Mukherjee; Satyavir Yadav; Subhradip Karmakar (Journal of Applied Genetics, 2026)

Worldwide assessment of green roofs retention using general linear models and multivariate adaptive regression splines - Inês Meireles; Verônica Brandão; Vitor Sousa; Ruby N. Michael; Ana Cláudia Dias (Sustainable Cities and Society, 2026)

Continuous reproduction facilitates the invasion success of the black mussel Mytella strigata in a tropical estuary - Robert Keith A. Sienes; Ma. Shirley M. Golez; Hessed T. Cabanilla; Michael H. Flores; Marienel A. Laguit; Paz Geneveve Q. Gacus; Junaisah Nissi L. Degoma; Delyn M. Bucay; Ruby C. Gonzales; Kaent Immanuel N. Uba (Regional Studies in Marine Science, 2026)

Corrigendum to “Phytolith spectra in respiratory aerial roots of some mangrove plants of the Indian Sunderbans and its efficacy in ancient deltaic environment reconstruction” [Quat. Int. (325), 19 March 2014, Pages 179-196] - Sayantani Das; Ruby Ghosh; Dipak Kumar Paruya; Yi-Feng Yao; Cheng-Sen Li; Subir Bera (Quaternary International, 2026)

Abiotic factors influencing the health of mature Araucaria heterophylla (Norfolk Island Pine trees) in urban coastal parks - Anna Petrova; Chris Pratt; Ruby Naomi Michael (Environmental Management, 2026)
Tree decline can significantly impact both the aesthetic value and ecological function of urban forests. Understanding the abiotic factors influencing tree health is essential for developing effective management strategies. This study investigated the decline of heritage Araucaria heterophylla (Norfolk Island Pine) in urban areas of the Gold Coast, Queensland, Australia, with a focus on identifying underlying abiotic causes. General assessment was conducted along a 5-km coastal strip (including 946 trees); climate conditions on the Gold Coast and Norfolk Island were compared; and 38 selected trees of varying health status were examined in detail. This included soil physicochemical and nutrient analysis, as well as foliar nutrient profiling. Results showed that 15.8% of the 946 initially assessed trees exhibited symptoms of decline, such as dieback, browning of foliage tips, extensive defoliation and shortened foliage length. Mean temperatures on the Gold Coast were consistently higher than those in the species’ native range and the current decline followed a period of elevated temperatures and reduced rainfall. Declining trees ( n = 32) from the subset population were found to be growing in compacted soils, with significantly elevated foliar sodium and lower foliar carbon levels compared to healthy trees ( n = 6), indicating possible disruption of nutrient regulation. Half of the trees in the advanced stage of decline were located less than 5 m away from carparks (50%), which was higher when compared with Moderate Decline (18.7%) and very healthy Benchmarking trees (0%). Most trees in the advanced decline category were not mulched and had turfgrass as the primary groundcover (62.5%), whereas trees in moderate decline were more commonly associated with turfgrass combined with fallen branchlets (43.75%). In addition, all Benchmarking trees were located in sandy soils, whereas declining trees were more commonly associated with loam soils, which are more susceptible to compaction. Key abiotic stressors identified were extreme weather and proximity to urban infrastructure. Management recommendations include improving root zone conditions by providing irrigation during dry periods, mulching, implementing routine health monitoring to support early intervention and, for new planting, increasing distances from hard infrastructure.

Correction: Neratinib-loaded solid lipid nanoparticles in dissolvable microneedles for enhanced transdermal breast cancer therapy - Saraisam Kishor Kumar Singha; Venkatesh Dinnekere Puttegowda; Yousef Al-ebini; Mohamed Rahamathulla; Joysa Ruby Joseph; Ajay Pankajbhai Lunagariya; Mohammed Jafar; Syeda Ayesha Farhana; Manjunatha Panduranga Mudughal; Gowdru Vishwanath Nahusha; Mohammed Muqtader Ahmed (Drug Delivery and Translational Research, 2026)

Neratinib-loaded solid lipid nanoparticles in dissolvable microneedles for enhanced transdermal breast cancer therapy - Saraisam Kishor Kumar Singha; Venkatesh Dinnekere Puttegowda; Yousef Al-ebini; Mohamed Rahamathulla; Joysa Ruby Joseph; Ajay Pankajbhai Lunagariya; Mohammed Jafar; Syeda Ayesha Farhana; Manjunatha Panduranga Mudughal; Gowdru Vishwanath Nahusha; Mohammed Muqtader Ahmed (Drug Delivery and Translational Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Pseudocapillaria tomentosa infections in laboratory larval and Adult Zebrafish (Danio rerio): Development and advances in an in vivo anthelmintic drug discovery model - Connor Leong; Ruby Scanlon; Aisling Kyne; Thomas J. Sharpton; Michael L. Kent (Veterinary Parasitology, 2026)

Well-designed construction of rare earth ruddlesden-popper oxide confined on reduced graphene oxide nanosheets: A promising electrocatalyst for the monitoring of anthropogenic toxin - Santhiyagu Sahayaraj Rex Shanlee; Muthukumar Govindaraj; Tse-Wei Chen; Shen ming-chen; Arockia Selvi J; Pichai Christina Ruby Stella; Safaa S. Taha; Mohamed Farouk Elsadek; Mohamed S. E. (Process Safety and Environmental Protection, 2026)

Genomic characterization of Salmonella enterica serotype Saintpaul isolates from horses - Tirth Uprety; Carrie L. Shaffer; Alan Loynachan; Jennifer Janes; Lynne Cassone; Laura Kennedy; Uneeda Bryant; Rebecca Ruby; Melissa Swan; Beatrice T. Sponseller; Emma Adam; Brian Lubbers; et al. (Veterinary Microbiology, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Monitoring beach face morphology from stereo satellite imagery - Shannon Brown; Annika O'Dea; Jeffrey Ruby; Erwin W.J. Bergsma; Rafael Almar; Katherine Brodie (Coastal Engineering, 2026)

Strategies to reduce cholesterol content in poultry eggs: an overview - Namrata Balhara; Dimple Dimple; Ruby Ruby; Andrew Magnuson; Arup Giri; Manishi Mukesh (Tropical Animal Health and Production, 2026)

Soil Application of Zinc for Potato Biofortification in the Central Andes of Peru - Fernando Chung-Montoya; Victorio Melendres-Herrera; Vanessa Pilatarzi-Vilchez; Angely Sinche-Ambrosio; Jesús Vera-Vilchez; Ruby Vega-Ravello; Sady García-Bendezú (Journal of Soil Science and Plant Nutrition, 2026)
Zinc is essential for human health, yet dietary deficiencies persist in many regions. This study evaluated the effectiveness of soil-applied zinc to enhance zinc content in potato tubers grown in Peru’s central Andes, as an agronomic biofortification strategy. Field trials were conducted over two seasons in four Andean sites using five Zn rates (0–32 kg ha⁻¹). One variety was tested in 2016–2017, and four in 2017–2018. Yield, Zn content, accumulation, partial balance, and dietary contribution were assessed. In both seasons, Zn fertilization did not significantly affect tuber yield. In 2016–2017, Zn content in tubers increased by up to 86% and accumulation by 74% at 16 kg Zn ha⁻¹. The estimated dietary contribution rose by 79%, with Achoscuyo showing the highest response and Lucma the lowest. Site differences were more evident at intermediate and high doses. In 2017–2018, Zn accumulation in shoots exceeded that in tubers by up to 2.8-fold, and Zn content in the peel was twice that of the flesh. Maximum Zn content and accumulation varied among varieties and doses. Canchán and Perricholi showed high Zn content and accumulation at 16 kg Zn ha⁻¹. Principal component analysis revealed that Zn dose was positively associated with Zn content and negatively with tuber yield. The response to Zn fertilization depended on site, dose, and genotype. Soil-applied Zn increased Zn content in potatoes without compromising yield. Selecting varieties with high tuber Zn accumulation improved nutritional outcomes and fertilizer use efficiency.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Navigating tricky trade-offs in busy seas: Insights from England for blue justice - Matt Fortnam; Liliana Bastian; Angela Phan; Océane Marcone; Tomas Chaigneau; Susan Kay; Sarah Sutcliffe; Rachel A Turner; Ruby Grantham; Aisling Lannin; Louisa Evans (Marine Policy, 2026)

When is a resprouter a resprouter? Improving terminology to reflect ecological thresholds for post-fire plant persistence - Ruby Paroissien; Ryan Tangney; Alexandria M. Thomsen; Catherine A. Offord; Mark K.J. Ooi (Science of The Total Environment, 2026)

Acute UV response of early erythema and late edema in SKH1 mice - Szabolcs Bozsányi; Rhea Carmel Glen Rodrigues; Ruby Acquah; Erin C. Tracy; Sean P. Murphy; Jocelyn Tracy; Li Yan; Mehdi Boostani; Hamid-Reza Rezvani; Wendy J. Huss; Gyorgy Paragh (Journal of Photochemistry and Photobiology B: Biology, 2026)

Pharmacokinetics and bioavailability of cefuroxime in Nile tilapia (Oreochromis niloticus) - Orhan Corum; Duygu Durna Corum; Pedro Marin; Onder Yildirim; Ertugrul Terzi; Ruby C. Gonzales; Dan M. Arriesgado; Victor R. Navarro; Soner Bilen; Adem Yavuz Sonmez; Kamil Uney (Veterinary Research Communications, 2026)

A holistic guide to effective prevention and treatment for kidney stones: a systematic review exploring anti-urolithiasis approaches - Anood T. Allam; Ahmed M. El-Dessouki; Riham A. El-Shiekh; Dina Abou-Hussein; Mahmoud Abdelmouti Mahmoud; Wagih H. Marcus; Hassan A. Ruby (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Urolithiasis, a disease of kidney stones, is a prevalent and recurrent condition characterized by the formation of hard mineral deposits in the urinary tract, leading to significant morbidity and a substantial healthcare burden worldwide. With recurrence rates ranging from 30 to 50% and a lifetime prevalence of 9–12% in industrialized populations, effective prevention and management strategies are crucial. Traditional approaches to urolithiasis, including pharmacological agents and surgical interventions, emphasize medical interventions and lifestyle changes; however, the persistent recurrence and impact on quality of life underscore the necessity for more comprehensive solutions. Recent advancements have focused on the potential of nutraceuticals, including herbal extracts, vitamins, and minerals, as adjuncts in the prevention and treatment of kidney stones. These agents may exert beneficial effects by inhibiting stone crystal formation, modulating urinary pH, reducing urinary calcium and oxalate excretion, enhancing diuresis, and supporting overall renal function. Moreover, these plant-based therapies may help alleviate symptoms such as pain and inflammation related to stone episodes. This systematic review synthesizes findings from 14 randomized controlled trials to assess the therapeutic impact and safety profile of various herbal interventions in patients with diagnosed kidney or ureteral stones. Thus, evidence from these recent clinical trials has increasingly supported the efficacy of single-herb and polyherbal formulations, such as Nigella sativa , Alhagi maurorum , Subap Plus, and Palasha Kshara, in modulating urinary risk factors and promoting stone expulsion. For instance, these trials demonstrated promising outcomes for several herbs: Portulaca oleracea significantly increased urinary citrate and reduced calcium, Traditional Persian Medicine-based Mofatet powder markedly reduced stone size and improved urinary parameters, Alhagi maurorum distillates and extracts showed comparable efficacy to hydrochlorothiazide in stone expulsion, and Nigella sativa performed as well as or better than tamsulosin in both pain relief and stone passage. Additional polyherbal remedies, such as Subap Plus, Palasha Kshara, and BNO 1040 extract, also yielded favourable results in improving stone clearance, easing symptoms, and potentially preventing recurrence. Notably, most studies reported good short-term tolerability and minimal adverse effects. Despite these promising findings, limitations in sample size, standardization of formulations, lack of comprehensive adverse events reporting, and need for long-term follow-up highlight the necessity for further rigorous trials.

Differential interspecific responses of symbiotic luminous bacteria Vibrio spp. in a cephalopod host to marine heatwaves - Eve Otjacques; Nicolina G. Ranieri; Tiago Repolho; José C. Xavier; Edward Ruby; Margaret McFall-Ngai; Rui Rosa (Marine Biology, 2026)

Environmental monitoring of carbofuran pesticides in wastewater, soil, and food samples using a Co9S8@N, S-doped carbon nanocomposite-engineered voltammetric sensor - Janagaraj Gandhiraj; Kavitha Balasubramanian; Michael Ruby Raj; Saradh Prasad; Khalid Eidah Alzahrani; Murugan Velmurugan; Chelladurai Karuppiah; Subramanian Chidambaravinayagam; Sayee Kannan Ramaraj (Environmental Geochemistry and Health, 2026)

Beyond understanding the role of far-field climate in the Gulf of Panama coastal dynamics: an analysis of long-term and seasonal variability of wave systems - Ruby Vallarino-Castillo; José A. A. Antolínez; Vicente Negro-Valdecantos; Jesús Portilla-Yandún (Climate Dynamics, 2026)
Understanding wave systems (WS) dynamics in semi-enclosed tropical basins is challenging due to interactions between remote wave generation and regional climate variability. In the Gulf of Panama, prior studies mainly relied on single-site offshore analyses, limiting characterization of wave energy distribution and its atmospheric and oceanic drivers. This gap in knowledge is particularly consequential for coastal hazard assessments and for deciphering ocean–atmosphere interactions in regions influenced by both long-period swells and low-level wind jets. To address this limitation, we present a comprehensive multi-decadal analysis of the seasonal and long-term variability of significant wave height (Hs) and peak wave period (Tp), based on WS identified applying spectral statistical techniques using the GLOSWAC-5 atlas. To understand the variability and the modulating effect of the Gulf of Panama semi-enclosed morphology, three representative sites at its entrance were selected. Monthly patterns were analyzed by classifying wave trains according to relative orientation (i.e., following, crossing, and opposing) to determine the predominant direction and multimodal activity. Long-term trends were assessed over 17 to 18-year intervals (i.e. 1969–1987, 1988–2005, 2006–2023) using exploratory analysis and quantile regression, with results reported separately for the dry season (December–April) and the wet season (May–November). The analysis revealed five dominant WS, each associated with specific generation mechanisms and geographic origins: WS1, associated with Southern Ocean swells; WS5, originating from Northern Hemisphere swells; WS2, driven by southeasterly trade winds from the subtropical Pacific; and two regionally forced systems, WS3 and WS4, generated by the Panama and Chocó Low-Level Jets, respectively. WS1 shows increases in Hs of about 5–10 cm during 1969–1987 and 1988–2005, and up to ~ 15 cm in 2006–2023, with Tp rising by ~ 0.3–0.6 s over the same intervals. WS2 exhibits small variations, with Hs ranging from − 10 to + 17 cm and Tp fluctuations within ± 0.3 s across the three intervals. WS3 displays the strongest changes, with median Hs increases of 10–30 cm in the first two intervals and extreme values reaching 50–60 cm in 1988–2005 and 2006–2023, together with Tp increments of ~ 0.3–0.5 s. WS4 remains comparatively stable in all periods, with Hs variations within ± 10 cm and Tp changes < 0.4 s. WS5 intensifies mainly in 2006–2023, showing Hs increases of 8–15 cm and Tp rises of ~ 0.2–0.4 s. Monthly mean Hs anomalies (> 0.10 m) at the 50th percentile suggest a relationship with El Niño–Southern Oscillation (ENSO), but analyses using the 95th percentile reveal that only WS2, WS3, and WS4 exhibit a stronger association with ENSO phases.

Marketing strategies used in retail food environments in Azerbaijan, Kazakhstan, and North Macedonia - Oliver Huse; Navoda Liyana Pathirana; Karan Courtney Haag; Ivan Durgutov; Akkumis Salkhanova; Elmir Valehli; Ana Paula Richter; Ruby Brooks; Clara Gomez-Donoso; Adrian J Cameron; Anna Peeters; Kathryn Backholer (Food Policy, 2026)

Advancing agrochemical surveillance: High-entropy MgFeCoNiZn layered double hydroxide for fenuron detection in soil and water - Chandini Ragumoorthy; Santhiyagu Sahayaraj Rex Shanlee; Shen-Ming Chen; Pichai Christina Ruby Stella; So-Qian Ching (Chemical Engineering Journal, 2026)

Praseodymium pyrochlore oxide/metal carbide dual-phase nanostructures: A high-performance platform for dimetridazole sensing across multiple matrices - Pandiyan Parkavi; Santhiyagu Sahayaraj Rex Shanlee; Shen-Ming Chen; Pichai Christina Ruby Stella (Chemical Engineering Journal, 2026)

Immune response precision customized to tumor adaptive kinetics - Yifan Li; Denisa Vlasceanu; Ruby Kim (BioSystems, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Robbers vs. invaders: The effects of alien tree invasions on nectar robbing in bird-pollinated Erica species - Ruby May Davies; Anina Coetzee; Colleen L. Seymour (Journal of Plant Research, 2026)

Constraints and promising interventions to strengthen fish seed systems in Sub-Saharan Africa: Evidence from Ghana - Catherine Ragasa; Froukje Kruijssen; Seth Koranteng Agyakwah; Emmanuel Tetteh-Doku Mensah; Ruby Asmah; Martha Ataa-Asantewaa; Sena Amewu; Sarah Alobo Loison (Agricultural Systems, 2026)

Multivariate environmental and trait-based controls of transpiration in the Central Amazon Rainforest - Yilin Fang; Cristina Santos da Silva; Adam Collins; Bruno O. Gimenez; Kolby Jardine; Robinson I. Negrón-Juárez; Regison Oliveira; Valdiek da Silva Menezes; Kurt Solander; Gustavo Spanner; Jeffrey M. Warren; Cynthia L. Wright; et al. (Agricultural and Forest Meteorology, 2026)